Cryo‐EM structure of MsbA in saposin‐lipid nanoparticles (Salipro) provides insights into nucleotide coordination. (27th December 2021) - Kehlenbeck, Dominique‐Maurice; Traore, Daouda A.K.; Josts, Inokentijs; Sander, Simon; Moulin, Martine; Haertlein, Michael; Prevost, Sylvain; Forsyth, V. Trevor; Tidow, Henning
Abstract : The ATP‐binding cassette transporter MsbA is a lipid flippase, translocating lipid A, glycolipids, and lipopolysaccharides from the inner to the outer leaflet of the inner membrane of Gram‐negative bacteria. It has been used as a model system for time‐resolved structural studies as several MsbA structures in different states and reconstitution systems (detergent/nanodiscs/peptidiscs) are available. However, due to the limited resolution of the available structures, detailed structural information on the bound nucleotides has remained elusive. Here, we have reconstituted MsbA in saposin A–lipoprotein nanoparticles (Salipro) and determined the structure of ADP‐vanadate‐bound MsbA by single‐particle cryo‐electron microscopy to 3.5 Å resolution. This procedure has resulted in significantly improved resolution and enabled us to model all side chains and visualise detailed ADP‐vanadate interactions in the nucleotide‐binding domains. The approach may be applicable to other dynamic membrane proteins. Abstract : The ATP‐binding cassette transporter MsbA was reconstituted in saposin A‐lipoprotein nanoparticles. MsbA was trapped in an ADP‐vanadate‐bound occluded state and its structure determined by single‐particle cryo‐EM to 3.5 Å resolution. This enabled us to build a complete model including all side chains and provided detailed insight into nucleotide coordination by the nucleotide‐binding domains.